2009
DOI: 10.1038/onc.2009.142
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilins contribute to Stat3 signaling and survival of multiple myeloma cells

Abstract: Signal transducer and activator of transcription 3 (Stat3) is the major mediator of interleukin-6 (IL-6) family cytokines. In addition, Stat3 is known to be involved in the pathophysiology of many malignancies. Here, we show that the cis-trans peptidyl-prolyl isomerase cyclophilin (Cyp) B specifically interacts with Stat3, whereas the highly related CypA does not. CypB knockdown inhibited the IL-6-induced transactivation potential but not the tyrosine phosphorylation of Stat3. Binding of CypB to Stat3 target p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 50 publications
3
69
0
1
Order By: Relevance
“…41,42 Although the direct correlation between expression of cyclophilins and phosphorylation of p38MAPK has not been established, increased levels of phosphorylated p38MAPK have been described in various cancers. 8,9,[12][13][14]35,43 In this study, we found that cyclophilinmediated isomerisation could be a critical step in the activation of p38MAPK, which could explain the correlative evidence in the literature concerning the overexpression of cyclophilins and an increase in p38MAPK phosphorylation. This in turn could suggest that different cyclophilins and in particular CypA can function as a molecular switch to modulate p38MAPK signalling to adjust to environmental changes, thus modulating cancer cell survival.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…41,42 Although the direct correlation between expression of cyclophilins and phosphorylation of p38MAPK has not been established, increased levels of phosphorylated p38MAPK have been described in various cancers. 8,9,[12][13][14]35,43 In this study, we found that cyclophilinmediated isomerisation could be a critical step in the activation of p38MAPK, which could explain the correlative evidence in the literature concerning the overexpression of cyclophilins and an increase in p38MAPK phosphorylation. This in turn could suggest that different cyclophilins and in particular CypA can function as a molecular switch to modulate p38MAPK signalling to adjust to environmental changes, thus modulating cancer cell survival.…”
Section: Discussionsupporting
confidence: 66%
“…32,33 Similar to CypA, genetic ablation of CypB reduces glioma cell survival and proliferation, as shown both in vitro and in vivo. 34,35 We found that multiple cyclophilins -CypA, CypB and CypH -directly interact with a newly identified target, p38MAPK, facilitating isomerisation of Pro224, which in turn is required to regulate phosphorylation of kinase regulatory Thr-Gly-Tyr motif. As a result, cyclophilin-mediated regulation of p38MAPK could be an additional way of controlling cell survival; as shown in Figure 6, both HeLa cells with downregulated CypA and transformed MEFs expressing an isomerisation-deficient p38MAPK are less viable when growing at clonal density.…”
Section: Discussionmentioning
confidence: 99%
“…It may be speculated that the interaction between CypA and SR-25 proteins may be involved in potential carcinogenic functions of CypA in HCC. Various PPIases have been reported to interact with transcription factors and to affect their activity (30,31). It can be speculated that the PPIase activity may be involved in the interaction between CypA and SR-25.…”
Section: Sr-25 Is Upregulated By Cypa Overexpression In Vitromentioning
confidence: 99%
“…CypB interacts with the transcription factor Stat3 in HepG2 liver cells which mediates the interleukin-6 family of cytokines [48]. Inhibition of CypB in Stat3-dependent human myeloma cell lines resulted in apoptosis, suggesting that CypB acts as a pro-survival protein in these cells [48]. Furthermore, CypB is overexpressed in malignant glioma tissue and suppression of CypB resulted in reduced cell growth and survival in vitro and in vivo [49].…”
Section: Introductionmentioning
confidence: 99%
“…Although members differ in substrate specificity, all PPIases catalyse the cis-trans conversion of X-proline peptide bonds cells decreased cell growth, proliferation and motility [47]. CypB interacts with the transcription factor Stat3 in HepG2 liver cells which mediates the interleukin-6 family of cytokines [48]. Inhibition of CypB in Stat3-dependent human myeloma cell lines resulted in apoptosis, suggesting that CypB acts as a pro-survival protein in these cells [48].…”
Section: Introductionmentioning
confidence: 99%